[Rezension von: Doe, Norman, 1957-, Comparative religious law : Judaism, Christianity, Islam] - Leigh, Ian (Journal of law and religion, 2020)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0748081420000478/resource/name/firstPage-S0748081420000478a.jpg